A new Lobosceliana Dirsh species (Orthoptera: Pamphagidae: Porthetinae) from coastal Tanzania, East Africa - Hemp, Claudia (Zootaxa, 2013)
A new flightless species of Lobosceliana is described from coastal Tanzania, East Africa. This is the first species within this genus with shortened wings in the male sex. The antennal formula is special in this species as well since it differs from that of other Lobosceliana species, questioning the systematic value of the number of antennal segments in Porthetinae as a useful generic character.